Implementation of Terminology Standards in Nursing Documentation Iin Healthcare: Scoping Review - Desak Kadek Sastrawati; NLP. Dina Susanti; Ni Luh Gde Nita Sri Wahyuningsih; Ni Nyoman Nuartini (Universitas Malahayati, 2026)
ABSTRACT Nursing care documentation is a document that contains the patient's condition starting from bio-psycho-social-spiritual assessment, nursing plan, intervention in accordance with the plan that has been prepared and evaluation carried out by nurses on patients from the patient's arrival to the patient's discharge. This scoping review aims to determine the application of terminology standards in health services. This study uses a scoping review. The search strategy used databases namely PubMed, ScienceDirect and Researchgate. The articles obtained were selected based on publications published between 2015-2025, the search used MeSH terms and PCC format in the selection of articles. A total of 15 articles describing the application of terminology standards in nursing care documentation were found. The use of international standards in European, American and African countries in preparing documentation are NANDA-I, NIC NOC, INCP, FinCC. While in Indonesia using NANDA, NIC NOC and SDKI, SLKI SIKI standards. However, the application of documentation using the SDKI, SLKI SIKI standards is still not optimal and nurses do not understand the practical implementation of the three standards. So referring to this, further study is needed in the future. Keywords: Nursing, Documentation, Standardize Terminology.